Baseline study on policy and governance gaps for the local government support fund assistance to municipalities (LGSF-AM) program: Integrated report - Charlotte Justine Diokno-Sicat; Catharine E. Adaro; Ricxie B. Maddawin; Angel Faye G. Castillo; Maria Alma P. Mariano (Philippine Institute for Development Studies (PIDS), 2020)
Despite almost three decades of Philippine decentralization, local governments continue experience varied levels of development and face challenges in delivering devolved basic services. At the same time, the national government has been continuously providing various forms of support for local governments to carry out devolved functions to build their capacity towards genuine fiscal autonomy. One major challenge faced in assessing the impact of the various interventions is the lack of baseline data. This current study aimed to identify policy and governance gaps in infrastructure and planning to provide baseline data on key areas and current planning practices of local governments to provide the necessary information for taking the next steps in decentralization. This report covers 1,373 municipalities and establishes baseline information on fiscal gaps in local roads, evacuation centers and rural health units. This study also documents governance gaps in development planning through a survey of planning practices vis-à-vis the DILGprescribed process of these municipalities. These are all done within the context of current local development instruments and performance monitoring systems reviewed during the initial stages of the drafting of this report. The desk review highlighted low revenue effort as well as inadequate utilization of mandated funds for development across municipalities. These facts contribute to delayed local development and have been attributed to poor planning such as lack of detail on development projects, lack of coordination and poor monitoring.
Keywords: 330; Governance gaps; comprehensive development plans; monitoring and evaluation; Philippine municipalities survey; programs projects and activities